Development of in-House Synthesis and Quality Control of [99mTc]Tc-PSMA-I&S - Elisabeth Plhak; Christopher Pichler; Edith Gößnitzer; Reingard M. Aigner; Herbert Kvaternik (Molecules, 2023)
Many radioactive PSMA inhibitory substances have already been developed for PET diagnostics and therapy of prostate cancer. Because PET radionuclides and instrumentation may not be available, technetium-99 m labelled tracers can be considered as a diagnostic alternative. A suitable tracer is [99mTc]Tc-PSMA-I&S, primarily developed for radio-guided surgery, which has been identified for diagnostics of prostate cancer. However, there is no commercial kit approved for the preparation of [99mTc]Tc-PSMA-I&S on the market. This work presents an automated process for the synthesis of [99mTc]Tc-PSMA-I&S concerning good manufacturing practice (GMP). We used a Scintomics GRP 4 V module, with the SCC software package for programming sequences for this development. The optimum reaction conditions were evaluated in preliminary experiments. The pH of the reaction solution was found to be crucial for the radiochemical yield and radiochemical purity. The validation of [99mTc]Tc-PSMA-I&S (n = 3) achieved a stable radiochemical yield of 58.7 ± 1.5% and stable radiochemical purities of 93.0 ± 0.3%. The amount of free [99mTc]TcO4− in the solution and reduced hydrolysed [99mTc]TcO2 was <2%. Our automated preparation of [99mTc]Tc-PSMA-I&S has shown reliability and applicability in the clinical setting.